An Exploration of Romance Formulas: The Film Can You Keep a Secret? by Sophie Kinsella - Nugroho, Aji Royan (Universitas Pendidikan Indonesia, 2025)
The research with Can You Keep a Secret? Film as an object material aimed to investigate the romance formula within this popular masterpiece. The popular work in this research is based on the same title by the writer Sophie Kinsella. This means the popularity is not just limited to the novel but continued throughout the film. The methodology of this research used qualitative description, which obtained the primary source from scenes of the film and the secondary source from references, books, and previous studies. How the elements and Roman formula are narrated, dominated become the main focus of this research to be analyzed. The result of this study showed that the Roman element narrated the whole story, which is dominated by romance and comedy, supported by the third figure. Meanwhile, the setting within the story uses romantic places, and the plot is easy to guess. Furthermore, the romantic element is followed by other films: a happy ending plot.